Effect of 20% ethanol extract of Subang pineapple gel on oral mucosa incisional wound length - Sabirin, Indah Puti Rahmayani; Polii, Amanda Debora; Khaerunnisa, Rahmadaniah; Yuslianti, Euis Reni; Kristiana, Ris (Padjadjaran Journal of Dentistry, 2022)
ABSTRACTIntroduction: Incisional wound in oral mucosa is usually performed during oral surgery but can also be caused by injury. Although wounds can naturally heal, the application of medicine might help accelerate wound healing. Proving the effectiveness of natural ingredients is currently being promoted because Indonesia owns many plants that are used empirically. The use of natural substances is also supported because it is relatively easy to obtain and safe if used properly. Subang Pineapple (Ananas comosus L. Merr) is one of the produce of West Java that people consume and empirically use on wounds. Its fruit and core contain active ingredients that affect wound healing, such as bromelain enzyme, flavonoids, saponin, and alkaloids. This study aims to determine the effect of fruit ethanol extract gel of Subang pineapple on Wistar rats oral incisional wound observed from wound length. Methods: 25 rats were divided into five groups: baseline, negative control, positive control with 10% povidone-iodine, positive control with AloclairTM gel, and treatment group with 20% pineapple ethanol extract gel used as wound model on the buccal mucosa. The length of the incisional wound area was examined on days 0, 3, 7, and 14. Measurement of wound length was performed using a periodontal probe. Results: The mean of wound length was smaller especially on day 3 in the treatment group. Post-Hoc Mann-Whitney test (p<0.05 considered significant) showed the wound decrease with Subang pineapple extract was better than the negative control (p=0.008) and povidone-iodine group (p=0.007) but didn’t show a significant difference with the Aloclair™ gel group (p=0.0118). Conclusion:  Topical application of pineapple extract affected oral mucosa incisional wound healing and had a potential to accelerate wound closure. Further study with different concentrations and another type of wound can be suggested.Keywords: incisional wound; pineapple extract; subang pineapple; wound healing